2021
DOI: 10.1016/j.jpurol.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of acute testicular torsion in the time of COVID-19

Abstract: Background Testicular torsion is a surgical emergency, and time to detorsion is imperative for testicular salvage. During the COVID-19 pandemic, patients may delay emergency care due to stay-at-home orders and concern of COVID-19 exposure. Objective To assess whether emergency presentation for testicular torsion was delayed during the COVID-19 pandemic, and whether the rate of orchiectomy increased compared to a retrospective period. Study Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 17 publications
1
38
1
6
Order By: Relevance
“…Both Littman et al and Nelson et al showed no significant alterations in orchiectomy rates of testicular torsion cases during the pandemic which this study was consistent with 11,12 . Contrarily, in the multicenter study by WPUC, significantly delayed patients during the pandemic resulted in a non-significant but numerically higher percentages of orchiectomies 13 . In this study, during the COVID-19 pandemic, the number and percentage of orchiectomies have decreased numerically but not significantly.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both Littman et al and Nelson et al showed no significant alterations in orchiectomy rates of testicular torsion cases during the pandemic which this study was consistent with 11,12 . Contrarily, in the multicenter study by WPUC, significantly delayed patients during the pandemic resulted in a non-significant but numerically higher percentages of orchiectomies 13 . In this study, during the COVID-19 pandemic, the number and percentage of orchiectomies have decreased numerically but not significantly.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to this study, Littman et al and Nelson et al found no delay in the time of presentation of testicular torsion cases during COVID-19 pandemic 11,12 . On the other hand, a very recent multicenter study from the Western Pediatric Urology Consortium (WPUC) suggests significantly longer presentation times of testicular torsion cases during the pandemic 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the association between COVID-19 and testicular torsion in the pediatric population [13][14][15]. Nelson [13]. These authors determined a significantly longer time from testicular torsion symptom onset to presentation during COVID-19 compared to pre-COVID-19 (17.9 hours vs 7.5 hours, p = 0.04) and a higher proportion of patients who reported a delay in presentation (46% vs 33%).…”
Section: Discussionmentioning
confidence: 97%
“…Gagliardi and colleagues described epididymoorchitis in a 14-year-old boy with COVID-19 without respiratory symptoms [29]. Few studies have reported the association between COVID-19 and testicular torsion in the pediatric population [13][14][15]. Nelson [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation